The Role of Sugar Transporter CsSWEET7a in Apoplasmic Phloem Unloading in Receptacle and Nectary During Cucumber Anthesis - Li, Yaxin; Liu, Huan; Yao, Xuehui; Sun, Lulu; Sui, Xiaolei (Frontiers in Plant Science, 2022)
During anthesis, there is an increased demand for carbohydrates due to pollen maturation and nectary secretion that warrants a systematic strategy for sugar partitioning. Sugar transporters are key components of the carbohydrate demand-supply system and control the sugar flux needed for plant development. Currently, it is poorly understood which sugar transporters are active during flower anthesis in cucumber. Here, we identified a hexose transporter that is highly expressed in cucumber flower, SWEET7a (Sugar Will Eventually be Exported Transporter 7a). The expression level of CsSWEET7a increased as the flower matures and peaked around anthesis in both male and female flowers. CsSWEET7a was mainly expressed in receptacle and nectary tissues, where its expression level increased rapidly right before anthesis. At anthesis, the CsSWEET7a protein was specifically localized to the phloem region of the receptacle and nectary, indicating that CsSWEET7a may function in phloem unloading during flower anthesis. A study utilizing the phloem-mobile symplasmic tracer carboxyfluorescein (CF) suggested that the phloem unloading was symplasmically isolated in the receptacle and nectary of cucumber flowers at anthesis. Although cucumber mainly transports Raffinose Family Oligosaccharides (RFOs) in phloem, monosaccharides and disaccharide were the major sugars in the flower receptacle and the nectary as well as in nectar at anthesis. These results indicated that CsSWEET7a may be involved in sugar partitioning as an exporter in the phloem of the receptacle and nectary to supply carbohydrates for flower anthesis and nectar secretion in cucumber.